2021
DOI: 10.30773/pi.2021.0057
|View full text |Cite
|
Sign up to set email alerts
|

Heart Rate Variability and Its Ability to Detect Worsening Suicidality in Adolescents: A Pilot Trial of Wearable Technology

Abstract: Objective Suicide is the 2nd leading cause of death in adolescence, and acute pediatric mental health emergency department (ED) visits have doubled in the past decade. The objective of this study was to evaluate physiologic parameters relationship to suicide severity.Methods This was a prospective, observational study from April 2018 thru November 2019 in a tertiary care pediatric emergency department (ED) and inpatient pediatric psychiatric unit enrolling acutely suicidal adolescent patients. Patients wore a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(29 citation statements)
references
References 28 publications
0
28
0
Order By: Relevance
“…Consistent with these findings, one of the two studies only included in the qualitative synthesis found that adolescents who displayed a decrease in suicidality over time displayed an increase in HRV at rest during night-time, but not during the day (Sheridan et al, 2021), whereas the other study found no group differences on RSA or PEP (Yang et al, 2019).…”
Section: Cardiac Measuresmentioning
confidence: 56%
“…Consistent with these findings, one of the two studies only included in the qualitative synthesis found that adolescents who displayed a decrease in suicidality over time displayed an increase in HRV at rest during night-time, but not during the day (Sheridan et al, 2021), whereas the other study found no group differences on RSA or PEP (Yang et al, 2019).…”
Section: Cardiac Measuresmentioning
confidence: 56%
“…The lack of studies on using PPG to evaluate other forms of mental health issues shows a clear gap in the literature. Preliminary studies, such as the one conducted by Sheridan et al [31], shows that PPG could be greatly beneficial for application in depression-specifically in detecting and intervening during acute suicidality-or for assistance in monitoring PTSD.…”
Section: Methods Classification Classesmentioning
confidence: 99%
“…There was only one paper was related to detection of suicidal behavior using PPG wearables [31]. In this study, 51 patients presented to the emergency department or admitted to the psychiatric unit for acute suicidality were asked to wear a PPG wristworn device for 7 days.…”
Section: Brief Summary Of Anxiety and Depression-related Papersmentioning
confidence: 99%
“…Twenty-one (50%) of the included articles were from North America, 12 (29%) [30,[46][47][48][49][50][51][52][53][54][55][56] from Europe, and 9 from Asia (21%) [49,[57][58][59][60][61][62][63][64]. The included studies were conducted in 15 different countries, most commonly in the USA (n = 20, 48%) [25][26][27][28][29][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45], India (n = 4, 10%) [57,58,61,63], and Netherlands (n = 3, 7%) [47,55,56]. A total of 32 (76%) articles were published between 2019 and 2022…”
Section: Demographicsmentioning
confidence: 99%